Thinking Style and Paranormal Belief: The Role of Cognitive Biases. (March 2022) - Williams, Chris; Denovan, Andrew; Drinkwater, Kenneth; Dagnall, Neil
This study investigated the degree to which cognitive bias mediated the relationship between thinking style and belief in the paranormal. A sample of 496 participants completed the Revised Paranormal Belief Scale (RPBS), the Belief in Science Scale (BISS), the Cognitive Biases Questionnaire for Psychosis, and the reality testing subscale of the Inventory of Personality Organization (IPO-RT). The BISS and IPO-RT served as proxy indices of preferred thinking style; the BISS assessed rational-analytical (objective) processing, and the IPO-RT intuitive-experiential (subjective) processing. Cognitive biases (Jumping to Conclusions, Intentionalising, Catastrophising, Emotional Reasoning, and dichotomous thinking) correlated positively with belief in the paranormal. Mediation using path analysis indicated that Emotional Reasoning and Catastrophising exerted indirect effects in relation to BISS, IPO-RT and RPBS. Direct relationships existed between IPO-RT and RPBS, and BISS and RPBS. Of the biases, only Emotional Reasoning and Catastrophising predicted RPBS. The contribution of Emotional Reasoning and Catastrophising to belief in the paranormal were consistent with previous research and the cognitive model of psychosis, which asserts that there are strong relationships between defective reality testing, emotional reasoning and delusional beliefs.